2014
DOI: 10.1155/2014/671956
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Study on the Modified Mechanism of Aluminum-Impregnated Bone Charcoal

Abstract: Fluoride contamination in drinking water is a prominent and widespread problem in many parts of the world. Excessive ingestion of fluoride through water can lead to the high risk of fluorosis in human body. Bone charcoal, with the principal active component of hydroxyapatite, is a frequently used adsorbent for fluoride removal. Many laboratory experiments suggest that the aluminum-impregnated bone charcoal is an effective adsorbent in defluoridation. However, the mechanisms underlying this modification process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Some less obvious absorption peak information was magnified. The strengthening of peak intensity in VIS–NIR was very important to the further exploration of its reflection mechanism ( Li et al, 2014 ). Compared with the conventional raw reflectance, FD, and SD, more spectral characteristics were refined of the spectrum reflectance treated by the pretreatment of fractional derivative, and are provided as Table S2 .…”
Section: Discussionmentioning
confidence: 99%
“…Some less obvious absorption peak information was magnified. The strengthening of peak intensity in VIS–NIR was very important to the further exploration of its reflection mechanism ( Li et al, 2014 ). Compared with the conventional raw reflectance, FD, and SD, more spectral characteristics were refined of the spectrum reflectance treated by the pretreatment of fractional derivative, and are provided as Table S2 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it should be noted that this is, of course, not the first study of inorganic materials using FTIR spectroscopy. Quite the contrary, FTIR is frequently used to characterize inorganic substances such as carbonates and silicates [9,10], metal-impregnated charcoal [11], minerals [12], and even functionalized ceramic membranes [13]. The novelty of the present work is the application of an FTIR method to the deposits from boilers and heat exchangers.…”
Section: Introductionmentioning
confidence: 99%
“…Elemental mass percentage of TBB700 before and after Cd 2+ adsorption Creative Commons Attribution-NonCommercial 3.0 Unported Licence. from the results observed by Li et al, who observed that the intensity of the peak increased aer adsorption because of the dissociation of hydroxyl ions during anion exchange 53. The intensity of peaks at 1411 and 1064 cm À1 associated with CO 3 3À groups played an important role in the removal of Cd 2+ by precipitation 14,54.…”
mentioning
confidence: 51%